Development of a Brief Adjusting Alcohol Purchase Task as a Measure of Behavioral Economic Demand for Alcohol in Two Samples of Heavy-Drinking Young Adults. - Coelho, Sophie G.; Belisario, Kyla L.; Keough, Matthew T.; Amlung, Michael T.; Murphy, James G.; MacKillop, James (Psychological Assessment, 2026)
Alcohol demand, reflecting the relative reinforcing value of alcohol, is robustly associated with alcohol use and problems. Alcohol demand is typically assessed using alcohol purchase tasks (APTs) in which participants estimate alcohol consumption at escalating prices, with the resulting demand curves yielding multiple indices of value. Although generally efficient, full-length APTs pose some burden and existing short forms cannot produce individual demand curves or derived indices. Thus, we developed a brief adjusting APT using an algorithm to identify 5–6 items from a full-length APT based on an individual's level of alcohol demand. Two independent samples of heavy-drinking young adults (Sample 1: N = 725, M = 21.43 years; Sample 2: N = 588, M = 22.64 years) completed an assessment that included a full-length APT and measures of alcohol use and problems. Using a binary-search-style algorithm, brief APT responses were extracted from the full-length APT. In each sample, individual demand curves from the brief APT fit the data well. Observed (intensity, O, breakpoint) and derived (elasticity) demand indices robustly corresponded with the full-length APT, including similar mean estimates and high correlations (r ≥ 0.79) between corresponding indices from the brief and full-length APTs. Demand indices from the brief APT were associated with alcohol use and problems, and associations of corresponding indices from the brief and full-length APTs with alcohol use outcomes were of equivalent magnitude. These findings provide initial support for a brief adjusting APT as a measure of alcohol demand. Future research should further evaluate this measure, including stand-alone administration and detection of within-person changes in alcohol demand. Public Significance Statement: The reinforcing value of alcohol (i.e., alcohol demand) is an important determinant of alcohol consumption and harms, and this study provides initial support for the validity of a brief measure of alcohol demand. Reducing participant burden relative to traditional fixed-item alcohol purchase tasks, this brief measure may permit more widespread assessment of alcohol demand, although further evaluation remains warranted.